A Woman Printer and Her Readers in Early Modern Transylvania - Czintos, Emese (Journal of Early Modern Christianity, 2016)
The printing press of Gáspár Heltai had an outstanding role in the popularization of the epic in verse ( históriás ének ), the most popular secular and vernacular literary genre of sixteenth century Hungarian literature, especially in the period when the press was taken over by the widow of the notable priest and printer. The paper treats the publishing activity Gáspár Heltai’s widow in comparison with her husband’s, based on the output of epic in verse of this printing press, investigating the reasons behind their changing agendas. The printing policies of the two printers are presented in a successive as well as a comparative approach, highlighting both the differences between, and the continuity of, their activity. The discussion of Mrs Heltai’s enterprise also fills a gap in the history of Hungarian typography, as long as the operation of the press after Heltai’s death is quite sketchily known. The paper also argues that Mrs Heltai was a successful businesswoman, while it also examines the possible audience of her many historical songs, hypothesizing about a possible female audience. Finally, the paper includes a brief overview of the afterlife of the Heltai-typography in the seventeenth century, trying to explain the decline of the genre.